The Role Of Supervisors And Standard Operating Procedures For Cleaning Rooms In Improving The Performance Of Employees Housekeeping Department Hotel Grand Mercure Medan - Husaini, Fachri; Dewi Shinta Wulandari Lubis (SEAN Institute, 2024)
The purpose of this study was to determine how the role of the Supervisor and the standard operating procedures for room cleaning in improving the performance of housekeeping department employees. This type of research is a type of qualitative research. In this study, data were collected through observation and in-depth interviews, research samples of supervisors at Grand Mercure Medan Hotel in the housekeeping department. The results of this study say that the role of supervisors and standard operating procedures (SOP) greatly affects employee performance so that employees can carry out SOP properly at work and with the role of supervisors and standard operating procedures can improve employee performance.